Effects Of Cyber Supply Chain Risk Management On Supply Chain Performance - Cheah , Kooi Boey (Universiti Sains Malaysia, 2015)
Manufacturing firms are very focus on their supply chain performance in order to satisfy customer demand and increase business profit.